The Influence of the Two Stay Two Stray Learning Model and Learning Motivation on Civics Learning Outcomes in Primary School Students - Sinaga, Risna; Perangi-angin, Reh Bungana Br; Simaremare, Aman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to determine the differences in the results of PPKn subjects for groups of students taught using the TWO STAY TWO STRAY and inquiry models, differences in the results of PPKn subjects for groups of students who have high and low learning motivation, and learning motivation in influencing the results of Civics subjects. This research was carried out at SDN 091713 Amborokan with class IV samples. This type of research is quantitative, using the experimental method (quasi-experiment) with a purposive sampling technique; the researcher chose class IV-A as the experimental class and IV-4 as the control class at SDN 091713. the sample in this study was taken as the entire population; class IV-A students had 32 students, and class IV-B had 32 students. In this case, the experimental class is class IV-A, which applies the Two Stay Two Stray learning model, while class IV-B is the control class, taught using the Inquiry learning model. In this research, analysis techniques are used with the steps of Descriptive Statistical Analysis, Inferential Statistical Analysis, Calculating the average, Calculating the standard deviation, normality test, homogeneity test, and hypothesis testing. The results of the research show that 1) there is an influence of learning models in influencing Civics learning outcomes with a calculated F of 59.805, 2) There is an influence of learning motivation in influencing Civics learning outcomes with a calculated F of 92.04, and 3) there is an interaction of learning models and Civics learning motivation with F count 4.09.